Pemberdayaan UMKM dan Kelompok Dasa Wisma Berbasis Teknologi Informasi di Desa Bangunjiwo Kabupaten Bantul - Zuhud Rozaki; Nur Rahmawati; Arie Kusuma Paksi; Yudhi Pramudya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Covid-19 pandemic has an impact on the economic sector. Many people are trying to survive because of the effects of this pandemic. This service activity aims to empower SMEs and the Dasawisma Group in Bangunjiwo Village, Bantul Regency, to be more developed and survive or recover from the impact of the pandemic. The methods used are training and mentoring. This service activity went well thanks to the cooperation of all partners. Efforts to increase the marketing capacity of partners are felt to have grown with this dedication. Partners have become aware that in a digital era like this, their business must be more up to date with the times and adaptive to existing problems. Dasa Wisma Group partners also experienced an increase in capacity, especially in processing food into frozen food. The hope is that partners can continue developing and adapting when problems like this pandemic arise.